PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS DISCOVERY LEARNING PADA POKOK BAHASAN LAJU REAKSI - Putri, Bella Listriani; Rery, R. Usman; Abdullah, Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The objective of this research was to develop the student’s activity sheet on reaction rate subject. This research was a reseach and development (R & D) with the 4-D model that comprise of Definition, Design, Develop, and Disseminate. It was only to developed phase and limited tryout. The research was located in FKIP Riau University. The students’ activity sheet were used as research objects based on discovery learning. The research was analyzed by descriptive statistic, that calculated by percentage of validation value. The average of four aspects of student’s activity sheet by validator’s team, such as properness of the content, languages, course and graphical were 90,50%,, 86,67%, 89,50%, and 93,75%, respectively. So, the average totality of student’s activity sheet based on the discovery learning was 90,37% that means valid criteria, the LKPD Developed was proper to use. In addition, the percentage of students response on LKPD was 90% with very good criteria.Keywords: Student Activity Sheet, Discovery Learning, and Reaction Rate.